Determination of phosphate levels in the southern part of Al-Hammar marsh water by flow injection analysis - Al-Sowdani , K.H.; Al-Jorany , Y.S. (Mesopotamian Journal of Marine Sciences, 2022)
Flow Injection Analysis (FIA) was applied to determine phosphate concentration in water of the southern part of Al-Hammar marsh water from July 2007 to July 2008. A linear line was obtained over the range 0.25- 1.75 μg/ml of phosphate with regression coefficient for seven points is 0.9999. The detection limit was 0.075 μg/ml with % R.S.D for ten replicate analysis of 1.0 μg/ml phosphate is 0.511% and the dispersion coefficient in the flow system is 5.4. The samples can be analyzed at rates exceeding 72 sample per hour .It was noted that phosphate concentration ranged 0.295 - 1.450 μg/ml, whereas the maximum phosphate concentration was recorded in spring 2008 and the minimum in autumn 2008.